Financial Literacy and Digital Payment Adoption as Determinants of Investment Intention: Evidence from the Jabodetabek Community - Intan Nura Anisah; Parulian Parulian (Talent: Journal of Economics and Business, 2026)
The rapid advancement of digital technology has significantly transformed investment behavior, particularly in relation to digital assets such as stocks and cryptocurrencies. In Jabodetabek, public participation in digital investment has increased alongside the widespread adoption of digital payment technologies. Nevertheless, this growing enthusiasm is not always supported by adequate financial literacy, which may expose individuals to irrational investment decisions and increased financial risk. This condition highlights the importance of financial literacy and digital payment adoption as key determinants of investment intention in the digital economy. This study aims to examine the effects of financial literacy and digital payment adoption on investment intention among residents of Jabodetabek. A quantitative research approach was employed using a survey method. The research population consists of Generation Z and millennial individuals residing in the Jabodetabek area who actively use digital payment services. A total of 86 respondents were selected through purposive sampling. Primary data were collected through a Likert-scale questionnaire, while secondary data were obtained from relevant literature. Data analysis was conducted using Structural Equation Modeling (SEM) based on Partial Least Squares (PLS-SEM) with SmartPLS 3.0 software. The findings of this study are expected to provide empirical insights into the role of financial literacy and digital payment adoption in shaping investment intention. Furthermore, the results may serve as a reference for policymakers, financial institutions, and educators in designing effective financial education programs and inclusive digital investment policies, particularly in the context of rapidly growing digital financial ecosystems.